Prediction of some peroxidase functions in Arabidopsis thaliana L. by bioinformatic search - A. S. Tugbaeva; A. A. Ermoshin; I. S. Kiseleva (Вавиловский журнал генетики и селекции)
Peroxidases of class III are common in various organisms. They are involved in lignin biosynthesis and plant protection against stressors. Peroxidases are presented in many isoforms, whose role is not always clear. The aim of this study is to analyze the amino acid sequences of reference peroxidases with known functions and peroxidases from Arabidopsis thaliana L. whose functions are unknown and to consider their putative roles in lignin biosynthesis. The structural and functional organization of peroxidases was analyzed by bioinformatical methods applied to open Internet sources. Seven reference peroxidases were chosen from four plant species: Zinnia sp., Armoracia rusticana P.G. Gaertn., Lycopersicon esculentum L. и Populus alba L. Twenty-four amino acid sequences of homologous peroxidases from A. thaliana were selected for the analyses with the BLAST service. Their molecular weights and isoelectric points were calculated. Multiple alignments of amino acid sequences and phylogenetic analysis were done. Sites of binding to monolignol substrates were identified in seven peroxidases from A. thaliana, and the enzymes were assigned to the groups of Sor G-peroxidases. Amino acid replacements in the primary structures of peroxidases were analyzed. Peroxidases from A. thaliana were clustered with reference peroxidases. They formed six clusters on the phylogenetic tree, three of which contained only A. thaliana peroxidases. Peroxidases within each cluster had similar molecular weights and isoelectric points, common localization of expression, and similar functions. Thus, the use of bioinformatics, databases, and published data bring us to assumptions as to the functions of several A. thaliana class III peroxidases. AtPrx39 peroxidase was shown to be affine to sinapyl alcohol; AtPrx54, to p-coumaryl and coniferyl alcohols. They are likely to participate in lignin biosynthesis.